EFFECTIVENESS OF OVINE FOLLICULAR FLUID AND EWE AGE ON IN VITRO NUCLEAR MATURATION AND EMBRYO EVOLUTION OF AWASSI EWES - Omar Mardenli; Ali A. Ibrahim; Ali S. A. Al- Tawash (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Two experiments were conducted to study the efficiency of the ovine follicular fluid (OFF) and the age of ewe on in vitro nuclear maturation of Awassi sheep oocytes (Experiment 1) and the subsequent stages of early embryos and their quality (Experiment 2). The OFF has been added to the basic maturation medium (TCM-199) with three different levels (A: 0% (Control group), B:15%, C:25% and D:50%) while the ages of the ewes were determined into two main groups (> 2 and 1-2 year). In the first experiment, across the two age groups, matured oocytes in C solution achieved the highest (p=0.006) rates of metaphase-II (85.70 and 82.35 % respectively). In the second experiment, oocytes belonging to > 2 and 1-2-year ewe age groups (C Solution) achieved the highest (p=0.001) rates of fertilization (23.17 and 30.73% respectively). Similar trend applies to the cleavage stage, the rates reached 35.14 and 41.27% respectively (p=0.01). No significant differences were noticed at the different stages of cleavage (2-4 cell, morula, and blastocyst). The resulting embryos of B (> 2-year ewe age group) and C solution (1-2-year age group) achieved the highest (p=0.04) rates of Type1 embryos (69.56 and 76.92% respectively). A significant difference was noticed in type2 embryos (p=0.02), embryos of the first and second age groups (Solution D) achieved the highest rates (46.15 and 33.33% respectively). It can be concluded that the adding of 25% OFF to the maturation media led to significant improvement in the rates of maturation, cleavage and type1 embryos of sheep oocytes.